Land restoration and socio-economic contribution of bamboo in Ethiopia - Abduselam Faris Abadega; Ibrahim Aliyi Abawaji (Brawijaya University, 2021)
Worldwide human activities are the driving force for land degradation; these difficulties will worsen without immediate remedial action. This pressing global issue affects mankind, especially rural communities. The indicators for land degradation is mostly reduction in benefits derived from land. Bamboo is a grass type with a very large woody stem. Bamboo forests are important both for land restoration and socio-economic value. This review paper is aimed to assess land restoration and socio-economic contributions of bamboo in Ethiopia. Ethiopia is the leading bamboo resource country in Africa. Assosa, Injibara, Gimbi, Ambo, Gurage, Bale, Masha, Chencha and Hagere-Selam are the known bamboo producing areas of Ethiopia. Basically, bamboo is considered a good plant for restoring degraded land and soil health. Bamboo has great benefits for income diversification and other socio-economic values. Additionally, bamboo plants have so many cultural and medicinal uses in many parts of Ethiopia. Though a variety of studies revealed that bamboo has a unique ability in restoring lands condition, but less attention was given for its biological soil conservation, so concerned body should create awareness regarding the importance of bamboo for soil and water conservation. Ethiopia has numerous hectares of natural bamboo, known in the African continent. But, the real benefits generated from this subsector is insignificant so, the concerned body should improve benefits obtained from bamboo. Bamboo production and processing provides job opportunities and creates economic and social stability, however, there is little attention given, and so concerned body should give special attention for this sub-sector.